2017
DOI: 10.1039/c6ra27063h
|View full text |Cite
|
Sign up to set email alerts
|

Stability, CO2 sensitivity, oil tolerance and displacement efficiency of polymer enhanced foam

Abstract: This paper focuses on the benefits of polymers that contribute to foam flooding, such as foam stability, carbon dioxide (CO2) sensitivity, oil tolerance and displacement efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 26 publications
1
24
0
2
Order By: Relevance
“…Simultaneously, CO 2 dissolves in the liquid films, which eventually leads to the phenomenon of coarsening. In addition, the microappearance of in situ foam is similar to that of the conventional foam generated by a high‐speed blender (Pu, Wei, & Sun, ), which indicates that a good texture can be developed in the in situ foam system.…”
Section: Optimization Of the Releasing Agentmentioning
confidence: 55%
“…Simultaneously, CO 2 dissolves in the liquid films, which eventually leads to the phenomenon of coarsening. In addition, the microappearance of in situ foam is similar to that of the conventional foam generated by a high‐speed blender (Pu, Wei, & Sun, ), which indicates that a good texture can be developed in the in situ foam system.…”
Section: Optimization Of the Releasing Agentmentioning
confidence: 55%
“…This conforms with the principle of the entry barrier stability coefficient (E) described in the Table 1. Pu et al (2017) also studied the relationship between the foaming concentration, surface tension, foam height and half-life. In their result (Figure 6), it can be observed that as the concentration of foaming agent increases, the foam height and foam half-life increased considerably, while the surface tension lowered.…”
Section: Eor-foam Half-lifementioning
confidence: 99%
“…When the CO 2 -brine system is strongly dispersive, more CO 2 will dissolve into the brine, and the dissolution process will be accelerated [17]. As the CO 2 solubility is enhanced under a supercritical state, it is expected that increasing pressure in deeper aquifers can greatly promote the solubility of CO 2 in aqueous solution [18]. Therefore, an adequate reservoir condition is important to reduce the time span of solubility trapping and will increase storage security [19].…”
Section: Introductionmentioning
confidence: 99%